2018
DOI: 10.3329/bpj.v20i2.37885
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Interactions of Valsartan, Glimepiride and Ciprofloxacin HCl by DSC and HPLC

Abstract: This article deals with the results of in vitro interactions among glimepiride, ciprofloxacin HCl and valsartan at the molar ratio of 1:1:1 by DSC and HPLC method. The DSC thermogram of the mixture (glimepiride, ciprofloxacin HCl and valsartan) showed different melting endotherm than the melting endotherm for standard valsartan, ciprofloxacin HCl and glimepiride. Since the melting endotherms of mixture and individual drugs were not identical, it demonstrated the presence of interactions among the drugs. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…In the current study, DM caused the elevation of MDA levels. The biological and pharmacological activities of the novel complexes of Dapg with Zn, Cr and/or Se ameliorated the hepatic functions and rejuvenated the antioxidant defense system [55]. The present study demonstrated that DM induced hepatotoxicity and severe oxidative stress, which could be mitigated by the administration of Dapg metal complexes with Zn, Cr and/or Se.…”
Section: Discussionsupporting
confidence: 51%
“…In the current study, DM caused the elevation of MDA levels. The biological and pharmacological activities of the novel complexes of Dapg with Zn, Cr and/or Se ameliorated the hepatic functions and rejuvenated the antioxidant defense system [55]. The present study demonstrated that DM induced hepatotoxicity and severe oxidative stress, which could be mitigated by the administration of Dapg metal complexes with Zn, Cr and/or Se.…”
Section: Discussionsupporting
confidence: 51%